Utilization Pattern of Personal Protective Equipment among Industrial Workers of Nawalparasi, Nepal - Acharya, Shiva Raj (Health Prospect, 2014)
Introduction: With industrialization, radical alterations in the life of many rapidly developing countries are visible. Lack of well designed and appropriate safety measures leads to serious adverse health consequences to the workforce. The concept of occupational safety and health is still new in Nepal. The main objective of the study was to assess the utilization of personal protective equipment among industrial workers in Chaudhary Group Industrial Estate, Nawalparasi. Methods: A descriptive, cross-sectional study was carried out among 187 workers of five industries (Beer, Rio, Chesseball, Chips and Wafer) of Chaudhary Group Industrial Estate, Nawalparasi. Results: Mean age of the workers involved was 34.09 years (SD: ±8.650). Nine out of ten (87.2%) workers used any kind of PPE while working in worksite. Association of use of personal protective equipment with gender and encourage to use of personal protective equipment were statistically significant while income, educational status, age and working experience remained insignificant. Conclusion: Majority of the workers used the personal protective equipment in Chaudhary Group of Industry. All workers of the industry should be aware on the use of personal protective equipment to get protected from any kind of adverse health effects/hazards during while working in the industry. DOI: http://dx.doi.org/10.3126/hprospect.v13i2.11833